2011
DOI: 10.1590/s0100-204x2011001200005
|View full text |Cite
|
Sign up to set email alerts
|

Promoção de crescimento e indução de resistência à antracnose por Trichoderma spp. em pepineiro

Abstract: Resumo -O objetivo deste trabalho foi determinar o efeito de 60 isolados de Trichoderma e do produto Trichodermil na promoção do crescimento e na indução de resistência sistêmica à antracnose, causada por Colletotrichum lagenarium em pepineiro, além de identificar as espécies dos isolados de Trichoderma spp. efetivas como indutores de resistência. Nos experimentos de promoção de crescimento, os isolados de Trichoderma spp. foram submetidos à inoculação no substrato e, após 21 dias, a massa de matéria seca da p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
18
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
5
18
0
13
Order By: Relevance
“…Similar results for peroxidase activity were obtained by Silva et al (2011), who observed the effect of 60 Trichoderma spp. isolates in induction of systemic resistance to anthracnose in cucumber plants.…”
Section: Biochemical Resultssupporting
confidence: 83%
“…Similar results for peroxidase activity were obtained by Silva et al (2011), who observed the effect of 60 Trichoderma spp. isolates in induction of systemic resistance to anthracnose in cucumber plants.…”
Section: Biochemical Resultssupporting
confidence: 83%
“…Therefore are reports of growth promotion by Trichoderma spp. in the absence of pathogens for other plant species such as tomato (Solanum lycopersicum L.) (Fontenelle et al, 2011), common bean (Phaseolus vulgaris L.) (Pedro et al, 2012), cucumber (Cucumis sativus L.) (Silva et al, 2011), and Arabidopsis sp. (Korolev et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Revista de Agricultura Neotropical, Cassilândia-MS, v. 4, n. 3, p. 97-102, jul./set. 2016Além do controle biológico, alguns isolados de Trichoderma têm sido referidos como promotores do crescimento vegetal pela habilidade que possuem na solubilização de fosfatos e outros minerais (KAPRI;TEWARI, 2010;SILVA et al, 2011), disponibilizandoos para as plantas, bem como, pela produção de auxinas(VINALE et al, 2008;OLIVEIRA et al, 2012), que…”
unclassified